Beyond the blockade: unmet needs in systemic targeted atopic dermatitis therapy - Zhang, Li; Peng, Ge; Wang, Mingyue; Niyonsaba, François; Gao, Xinghua (Frontiers in Immunology, 2025)
Current atopic dermatitis treatments have been revolutionized by systemic targeted therapies that modulate inflammatory cytokine signaling pathways. While agents such as Janus kinase inhibitors and interleukin-4/interleukin-13 pathway inhibitors have shown significant efficacy, unmet needs persist. These needs include challenges in achieving stable disease control and remission, addressing nonresponders, managing potential side effects, and alleviating the ongoing struggle with pruritus. Future directions will focus on developing dual/multitarget drugs, creating longer-acting formulations, improving administration convenience, reducing dosing frequency, identifying novel therapeutic targets, and incorporating patient-reported outcomes in clinical assessments.